1994
DOI: 10.1007/bf02540665
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of palm acid oil

Abstract: Palm acid oil (PAO) is a by-product obtained from the alkaline refining of palm oil. It is used for making laundry soaps and for producing calcium soaps for animal feed fo~ mulations. The properties and composition of PAO may differ according to variations in the palm oil feedstock and the alkaline refining process. Because information on the characteristics of PAO is limited, this investigation aims to establish the properties of this product. Quality and oxidative parameters of 27 samples of PAO were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…First, regarding primary oxidation, no differences were encountered between AO and FAD groups, and neither of them presented samples with high PV, which agreed with those results previously found by Nuchi et al [19] for similar byproducts. Moreover, Kuntom et al [42] found PV values in PFAD below 5 meq O 2 /kg in most samples, except for two outliers with PV above 10 meq O 2 /kg. As a primary oxidation parameter, PV measures lipid hydroperoxides, which are unstable at high temperatures.…”
Section: Influence Of the Refining Process (Ao Vs Fad)mentioning
confidence: 94%
“…First, regarding primary oxidation, no differences were encountered between AO and FAD groups, and neither of them presented samples with high PV, which agreed with those results previously found by Nuchi et al [19] for similar byproducts. Moreover, Kuntom et al [42] found PV values in PFAD below 5 meq O 2 /kg in most samples, except for two outliers with PV above 10 meq O 2 /kg. As a primary oxidation parameter, PV measures lipid hydroperoxides, which are unstable at high temperatures.…”
Section: Influence Of the Refining Process (Ao Vs Fad)mentioning
confidence: 94%
“…It is used for making laundry soaps and for producing calcium soaps for animal feed formulations. The main components of Palm Acid Oil (PAO) are free fatty acids, neutral oil and moisture (Kuntom et al, 1994). Palm Acid Oil proves to be a suitable candidate for the base material for lubricant as it has very high Free Fatty Acid contents is not edible and is costbeneficial as the current uses are few.…”
Section: Resultsmentioning
confidence: 99%
“…Palm acid oil is a side product from the palm oil alkaline refining process, which consists of primarily free fatty acids up to 62.6% and neutral oil with moisture content < 2%. 155 Moreover, fatty acids have a higher number of carbon atoms (C > 10), such as lauric, myristic, palmitic, and stearic acids from palm oil, which are known as non-toxic, environmentally friendly, and renewable materials. 156 Thotakura et al reported on the preparation and properties studies of polymeric micelles from chitosan-palmitic acid for tamoxifen drug delivery.…”
Section: Miscellaneous Polymersmentioning
confidence: 99%